Clinical value of NT-proBNP, MPO, and NLR combined with echocardiography in prediction of malignant arrhythmia in elderly patients with valvular heart disease - Jianping Liu; Apei Zhou; Meiduan Zheng; Ling Wang; Ping Zeng (Perioperative Medicine)
Abstract Objective We aimed to probe the clinical value of N-terminus pro-brain natriuretic peptide (NT-proBNP), myeloperoxidase (MPO), and neutrophil lymphocyte ratio (NLR) combined with echocardiography in the prediction of malignant arrhythmias (MA) in elderly patients with valvular heart disease (VHD). Methods MPO, NT-proBNP, and NLR were detected in blood samples. After 1 year of follow-up, receiver operating characteristic curves were analyzed to determine the clinical value of NT-proBNP, MPO, NLR, and echocardiography for predicting MA in patients with VHD. Results MPO, NT-proBNP, and NLR were higher in the VHD group. MPO, NT-proBNP, and NLR were higher with severe cardiac dysfunction. MPO, NT-proBNP, NLR, and LVESV in the MA group were higher. NT-proBNP was an independent factor influencing the occurrence of MA in elderly patients with VHD. The AUC for predicting MA in elderly patients with VHD using NT-proBNP, MPO, NLR, and echocardiography were 0.782 (sensitivity 61.50%, specificity 94.60%, 95% CI 0.630–0.934), 0.759 (sensitivity 69.20%, specificity 81.10%, 95% CI 0.579–0.938), 0.736 (sensitivity 76.90%, specificity 64.90%, 95% CI 0.562–0.910), and 0.782 (sensitivity 76.90%, specificity 75.70%, 95% CI 0.646–0.918), respectively. The AUC for the combined prediction using NT-proBNP, MPO, NLR, and echocardiography was 0.913 (sensitivity 76.90%, specificity 94.60%, 95% CI 0.820–1.000), higher than that of each parameter alone (P < 0.05). Conclusion The combination of NT-proBNP, MPO, NLR, and echocardiography has a predictive value in detecting MA in elderly VHD patients.